Protection Bilateral Investment Treaty as Treaty of International Discussion Resolution Supporting Indonesia Reform - Ningsih, Ayup Suran; Niravita, Aprila; Masyhar, Ali; Suhadi, Suhadi; Bin Hassan, Muhammad Sayuti; Sulistianingsih, Dewi; Shidqon Prabowo, Muchammad; Ramli, Asmarani; Wedhatami, Bayangsari; Maharani, Ferra Tiara; Wardhani, Harumsari Puspa (Susbtantive Justice International Journal of Law, 2024)
The implementation of the Bilateral Investment Treaty in Indonesia with foreign investors must still pay attention to the existence of Indonesian state sovereignty. State sovereignty must be maintained by the host state to maintain the existence of the country in the international world. BIT has the main function as an international legal instrument that is useful in foreign investment activities with reciprocal relations in obtaining benefits between the guarantee of legal protection of the home state of foreign investors and the economic growth of the host state. BIT signatories are theoretically balanced and reciprocal, but they are often detrimental to host states, most of which come from developing countries. This research aims to find out the extent of Indonesia's implementation of BIT and still protect the existence of state sovereignty. The method used in this research uses normative and comparative juridical and this research has an analytical descriptive nature. Normative legal research is obtained by studying the Churchill Mining case approach and collecting data from articles, web, books, and websites and then comparing the implementation of BITs in Indonesia as a developing country and the United States as a developed country and comparing the implementation of BITs in fellow developing countries between Indonesia and Brazil. The first victory achieved by Indonesia against Churchill Mining in the resolution of the international investment dispute at the ICSID forum proved the BIT reform in Indonesia that continues to develop. This study showed that: first, The Bilateral Investment Agreement provides legal protection guarantees for foreign investors and settlement of settlement disputes through ICSID, an international investment settlement arbitration agency between the two countries that signed the BIT so that the BIT is a protection guarantee for investors. Second, Indonesia's victory against Churchill Mining proves that it has reformed the BIT that applies to Indonesia in a balanced manner to provide legal protection (host state) and the existence of state sovereignty (home state).